The Plaho Ritual: Cultural Study on Siulak Community, Kerinci Regency - Yolla Ramadani; Salamah Salamah; Suci Marselina (Indonesian Journal of Religion and Society, 2022)
The Plaho ritual is a tradition tribute to the spirits of ancestors who have died long ago by providing food offerings such as white rice, yellow rice, black rice, brown rice, chicken eggs, duck eggs, roasted sticky rice called lemang, roasted chicken, orange juice, various flowers, betel leaves and etc. This ritual is carried out when people in the community suffer from misfortune, illness, have no offspring or no sustenance, or when they want to make a pledge in order to avoid misfortune, have success in trading, produced a lot of agricultural products, and so on. This ethnographic research was using an interpretive theoretical analysis proposed by Clifford Geertz and was conducted in the Siulak community, Kerinci Regency. Informant selection technique was carried out by using a deliberate selection of informant namely purposive sampling technique. Data collected through observation and in-depth interviews were then analyzed using interpretive analysis with steps as follows: data hermeneutic, data interpretation, and interpretative representation. This research results reveals that the Plaho ritual is still carried out by Siulak community since they believe that by carrying out this ritual, they will be protected from all disasters and dangers threatening their social life and that not all diseases can be treated medically. Plaho ritual to Siulak community also has a separate function which indirectly is a form of respect for their ancestors, as a cultural inheritance, as a form of retreat, a reminder of death, and a means of social integration, which purpose is none other than to get oneself closer to The Almighty God.